ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2021
DOI: 10.1109/icassp39728.2021.9414278
|View full text |Cite
|
Sign up to set email alerts
|

Independent Sign Language Recognition with 3d Body, Hands, and Face Reconstruction

Abstract: Independent Sign Language Recognition is a complex visual recognition problem that combines several challenging tasks of Computer Vision due to the necessity to exploit and fuse information from hand gestures, body features and facial expressions. While many state-of-the-art works have managed to deeply elaborate on these features independently, to the best of our knowledge, no work has adequately combined all three information channels to efficiently recognize Sign Language. In this work, we employ SMPL-X, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…hand gesture, body pose, and facial expression. The authors in [24] utilized SMPL-X, a modern parametric model that allows the extraction of 3D body shape, face, and hand information from a single image. By using this comprehensive 3D reconstruction, the authors conducted SLR and found that it resulted in greater accuracy compared to recognizing information from raw RGB images or 2D skeletons.…”
Section: A Depth Pose Alignment Of Imagementioning
confidence: 99%
“…hand gesture, body pose, and facial expression. The authors in [24] utilized SMPL-X, a modern parametric model that allows the extraction of 3D body shape, face, and hand information from a single image. By using this comprehensive 3D reconstruction, the authors conducted SLR and found that it resulted in greater accuracy compared to recognizing information from raw RGB images or 2D skeletons.…”
Section: A Depth Pose Alignment Of Imagementioning
confidence: 99%
“…It is also recognized for independent sign language, comprising a 3D body, hands, and facial expressions. For this purpose, SMPL-X extracts features of body shape, face, and writing using a single image [14]. The 3D reconstructed output of the 3D model is utilized for SLR resulting in higher accuracy than raw RGB images.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Yang et al [70] generate sequences of body language predictions from estimated human poses and feed them to an RNN for emotion interpretation and psychiatric symptom prediction. Kratimenos et al [32] extract a holistic 3D body shape, including hands and face, from a single image and feed them also to an RNN for sign language recognition. Singh et al [61] use handcrafted features to analyze body language for estimating a person's emotions and state of mind.…”
Section: Namementioning
confidence: 99%